(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The modern world is characterized by significant transformations that affect various social institutions, among which one of the most powerful is the sphere of physical culture and sports. For many centuries, physical culture and sports have been functionally adapting to the needs and demands of society, its structure, which is constantly changing. The emergence of physical culture begins from the moment when our ancestors began to use physical exercises for the sake of their existence in the struggle against the forces of nature. The purpose of the study is to characterize the content of the theory of labor activity in relation to the emergence of physical culture. To achieve the goal of the study, a complex of interrelated research methods was used, namely: analysis, synthesis and generalization of scientific information on the research problem, educational and methodological literature and Internet sources. Physical culture, like culture in general, is the result of the socio-historical practice of people. In the process of work, people, influencing the nature surrounding them, at the same time change their own nature, developing their physical and spiritual forces. The results of the study proved that the theory of labor activity is based on the assumption that a person’s physical skills were formed under the influence of the need to perform labor tasks for survival and productive work. In the theory of labor activity, G.V. Plekhanov and M.I. Ponomarev distinguish objective and subjective factors in relation to the emergence of physical culture. The objective factor includes the fact that in the process of labor activity a person was constantly forced to develop their skills. The subjective factor includes the consciousness of a person who formed exercises to prepare for labor activity, establishing a connection between preliminary training and the results of hunting, and also organized the transfer of experience of acquired skills. The results of the study show that the theory of labor activity provides a logical explanation for the emergence of physical culture. She emphasizes that the physical development of man was directly related to labor processes that required strength, endurance, and coordination.